Divorce as a mode to resolve matrimonial conflict - the first or the last resort? - Abd Malek, Normi (Malayan Law Journal Sdn Bhd, 2010)
Marriage is a sacred relationship not only imbued with love, but also with rights and responsibilities. Every man or woman entering into a marriage contract would wish that no serious conflict could affect that relationship. Both parties would expect that the ship will sail smoothly and safely until it reaches its final destination. Nevertheless, a conflict in a marriage may still arise due to many factors. The question is: how should one face this challenge? Islam has provided ways to resolve matrimonial conflicts. It is undeniable that divorce is one of the methods to resolve the problem, but this is not the first mode of dispute resolution that one should resort to. The Quran provides direct and indirect modes of resolving conflicts. For example, patience and contemplation are among the important attributes recommended in order to seek the way out as indirectly stipulated in surah An-Nisa’, verse 19. In dealing with a nusyuz (recalcitrant) wife, Islam teaches its followers to abide by three important steps that should be taken before proceeding to other courses. They are: to advise the wife with full kindness, to refuse sharing a bed with her and finally to beat her lightly as a way of teaching, but of course, not with the intention to harm her. Should this method fail to produce a positive outcome, counseling by family members or professional people would be the next best course. This paper aims to highlight the steps provided by Islamic Law in order to resolve conflicts arising from a matrimonial relationship. It will also elaborate on the role of the couple as the key player, family members and judges in their attempt to deal with the conflict.